Formation of Polymeric Assemblies of Six-Coordinate Metal Complexes with Mixed Bridges of Dicarboxylato-Azido - Ahmed, Riyadh M; Himdan, Taki A; Numan, Ahmed T; Al-Jeboori, Mohamad J (Al-Nahrain Journal of Science, 2014)
New polydentate ligand namely bis(N-carboxylatoethyl)-4,4`-dipyridinium) L was synthesised from the reaction of 4,4`-dipyridine with ethyl chloropropionate. Polymeric complexes of general formulae [Cr2(L)(N3)4]Cl2.H2O, Na2[Ag2(L)(N3)4].H2O and [M2(L)(N3)4].nH2O, where (M= Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II); (where n = 2;1;1;1;0;1 and 1, respectively)) are reported. The mode of bonding and overall geometry of the complexes were determined through physico-chemical and spectroscopic methods. These studies revealed octahedral geometry complexes. Molecular structure for the complexes has been optimised by CS Chem 3D Ultra Molecular Modelling and Analysis Program and supported a six coordinate geometry.